Era society 5.0: Kecanggihan teknologi pada sektor industri dan dampaknya terhadap psikologis masyarakat - Rahmawati, Ainia Fikri (Maliki Interdisciplinary Journal, 2024)
The development of increasingly sophisticated technology affects various aspects of life. In the industrial world, technological sophistication can increase efficiency and productivity. However, emerging renewable technologies cause fear in society. This research aims to examine the forms of threats or challenges that can affect people’s psychology related to the existence of sophisticated industrial technology in the era of society; the types of individuals in responding to it; and the steps that can be taken to deal with the risks. This research is a qualitative research with descriptive method through literature approach. The results found that there are challenges or threats to the loss of several types of jobs that exist today along with technological sophistication in the industrial sector due to job shifts by AI, automation, and robotization. In response, there are individuals with a negative perspective due to concerns about job loss (individuals who lack skills) and individuals with a positive perspective (highly skilled). Thus, people need to adapt and develop new skills through education and training. Along with this, the government must also develop social and economic policies in the form of retraining for affected workers and infrastructure development to support job transformation caused by AI development.